Pendampingan Pemilihan Jajanan Sehat sebagai Upaya Pencegahan Obesitas pada Anak Usia Sekolah - Yulistianingsih, Ari; Firdaus, Asep Novi Taufiq (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
High-calorie snacks triggers the accumulation of fat in the body which can cause overweight and obesity in children. In addition, high-calorie snacks intake affects academic performance. Based on preliminary study, 57% of primary school students consume high-calorie snacks. In addition, the lack of healthy canteen facilities triggers children to buy food outside of school. Based on initial observations, 80% of food vendors sell high calorie and simple sugars snacks. This community service aims to assess the effectiveness of assistance to school children's knowledge as an effort to prevent obesity. This study used the PAR (Participatory Action Research) approach through the lecture method using animated videos, peer groups and demonstrations. Results shown that nutrition mentoring program can increase nutrition knowledge in primary school-aged children by 55%. It was concluded that mentoring the selection of healthy snacks for school children can increase knowledge in preventing obesity.